Farmer’s Perception and Adoption Level of Technology Application by Bio-Industrial Agricultural Model Based on Integrated Beef Cattle Husbandry with Corn Crops - Dahya, Dahya; Karimuna, Siti Rahmah; Rusdin, Rusdin; Bungati, Bungati (Universitas Halu Oleo, 2023)
A bio-industrial farming system is a system that optimally manages and utilizes all biological resources, including biomass and organic agricultural waste, for the welfare of the community in an ecosystem in harmony. Integrating plants with livestock is one way to utilize all the waste produced from corn and cattle optimally, so it is a solution in providing organic fertilizer and feed during the dry season. This study aims to determine the perception, level of adoption, and adoption trend on the Bioindustrial Agriculture Model based on beef cattle integrated with corn at the farmer level. The research was conducted from August to December 2019 in Pangan Jaya Village, Lainea District, South Konawe Regency. Data was collected through interviews with 30 farmers with a structured question guide (questionnaire). Data were analyzed descriptively. The results showed that farmers positively perceive the technological innovation of corn and livestock. Farmers consider technological innovation in the Bioindustrial Agricultural Model profitable, uncomplicated, easy to try and see the results, does not conflict with local traditional values, and is by community needs. The level of adoption of technological innovations in the Bioindustrial Agriculture model is in the high category, reaching 67.14%. The adoption trend indicates that some technology components that farmers have not adopted will be adopted in the next growing season. Keywords: technological innovation, organic fertilizer, feed, and questionnaire